Tourism and social vulnerability. Reflections for some Latin American cases - Vianchá-Sánchez, Zulma (2021)
Tourism is considered a way out of poverty and a generator of contexts of social vulnerability because it develops in diverse contexts and territorial conditions, which generate results ambivalent. In Latin America, social structures and inequities increase the vulnerability of host communities, which is why the impacts of tourism are not always beneficial. This article analyzes the transformation processes that emerge because of the configuration of tourist destinations and their complex interrelationships and impacts. The review was carried out from searches of cases in Latin American in the SCOPUS database, then a case in Mexico and Colombia was selected to deepen these transformations. The study made it possible to identify that the impacts most referenced in the research are negative,  particularly related to the destruction and loss of resilience of ecosystems, the increase in the social vulnerability of the livelihoods of local communities, the increase in conflicts due to the access and use of natural resources and inequality in the distribution of costs and benefits of tourism.